Arah dan Orientasi Filsafat Ilmu di Indonesia - Mardinal Tarigan; Dinda Gustiana; Tiara Dwi Lestari; Qorri Fadhilah; Yulia Hidayat (Universitas Muhammadiyah Enrekang, 2022)
Filsafat Ilmu is one of the specific Filsafats that has a strategic position in Indonesia's development of the ilmu paradigm. Filsafat's position in the evolving paradigm of knowledge will be examined in this research. Some of the things that were discussed in this study are listed below. In Indonesia, Filsafat Ilmu is a paradigm and a way of life. At addition, Filsafat Ilmu students in Indonesia's kuliah madrasah are encouraged to read and learn about the school's many books of poetry and prose. Filsafat Ilmu is a discipline of the Indonesian Filsafat that is gaining traction. The purpose of this study is to analyze and decipher the aims and progress of Filsafat Ilmu in Indonesia from the perspective of the paradigm of ilmu and the history of its transmission through Indonesian books and scholarly articles. It is used in the study of Filsafat Ilmu to use a method of research known as kualitatif, which involves analyzing the sources or data from books, journals, documents, and textbooks. Interpretation, heuristics, and philosophical reflection are all forms of analytic methods used. Research shows that Filsafat Ilmu is being developed and taught in line with the current paradigm for Filsafat Ilmu. It is this structure that was built to help grow Filsafat Ilmu, starting with the fundamental understanding of Filsafat's fundamentals all the way down to its core tenets. Orientasi Flsafat Ilmu, a discipline derived from the Filsafat that was developed in Indonesia from a variety of literature, still dominates on the orientation of Filsafat barat.